PEMBERDAYAAN PEREMPUAN MELALUI KEGIATAN SEKOLAH KELUARGA DI KOTA BUKITTINGGI - Nini Chania; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Limitations in knowledge, as well as differences between men and women, make women in Indonesia even more powerless. The family has a very important role in increasing development, the presence of family schools is an innovation in community education services in the form of guidance and improvement in improving the quality of the family in increasing the knowledge, skills and attitudes of parents and other family members in fostering growth in a comprehensive and integrated manner in order to achieve optimal growth and development. The purpose of this study was to determine the empowerment of women through family school activities in increasing family resilience in the City of Bukittinggi and find out supporting and inhibiting factorsfor women's empowerment through family school activities. The method used is qualitative methods with data collection techniques carried out by observation, interviews, and documentation. Informants were taken using purposive sampling and snowball sampling. The result of this research is that women's empowerment through family school activities in the city of Bukittinggi has not been running optimally, based on equality, community participation, self-reliance and sustainability. The driving factor in empowerment through family school activities is support from related parties, then the inhibiting factor is the facilities and infrastructure and the community's mindset.  Keywords: Women's Empowerment, Family School Activities